Well-formed Model Co-evolution with Customizable Model Migration - Mantz, Florian; Taentzer, Gabriele; Lamo, Yngve (Electronic Communications of the EASST, 2013)
Model-driven engineering (MDE) is a software engineering discipline which focuses on models as the primary artifact of the software development process while programs are mainly generated by means of model-to-code transformations. In particular, modeling languages tailored to specific domains promise to increase the productivity and quality of software. Nevertheless due to e.g. evolving requirements, modeling languages evolve and existing models have to be migrated. Corresponding manual model migration is tedious and error-prone, therefore tools have been developed to (partly) automate this process. We follow the idea of considering such modeling language and model co-evolutions as related graph transformations ensuring a correct and unique typing of migrated models. In this paper, we present a general and formal construction of well-formed model migration schemes that are able to co-adapt any model of a given modeling language to a performed meta-model change. We show how appropriate model migration schemes can be constructed and discuss how they may be customized.